PENGARUH PROFITABILIAS, LIKUIDITAS, LEVERAGE, DAN UKURAN PERUSAHAAN TERHADAP KETEPATAN WAKTU PENYAMPAIAN LAPORAN KEUANGAN PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2015-2017 - Dewi Lestari, 15.05.52.0195; Anggana L, Gregorius (Students' Journal of Accounting and Banking, 2019)
Timeliness of financial reporting is a characteristic that is important to the financial statements. This study aims to examine the effect of profitability, liquidity, leverage, and firm size on the timeliness of financial statement disclosures in manufacturing companies listed on the Indonesia Stock Exchange for the period 2015-2017. Sampling in this study used a purposive sampling method, so the companies included in the criteria were 428 companies. The data analysis method used in this study is logistic regression analysis. The results of this study indicate that the variable profitability has no significant positive effect on the timeliness of financial statement disclosures. Leverage variables have a significant negative effect on the timeliness of financial statement disclosures. Liquidity variables and firm size variables have a significant positive effect on the timeliness of financial statement disclosures.